2012
DOI: 10.1016/j.lungcan.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vitamin D receptor (VDR) in lung adenocarcinoma

Abstract: Purpose The anti-proliferative effects of 1α,25-dihydroxyvitamin D3 (1,25-D3, calcitriol, the active form of vitamin D) are mediated by the nuclear vitamin D receptor (VDR). In the present study, we characterized VDR expression in lung adenocarcinoma (AC). Experimental Design We examined VDR mRNA expression using a quantitative real-time PCR (qRT-PCR) in 100 patients who underwent surgery for lung AC. In a subset of these patients (n = 89), we examined VDR protein expression using immunohistochemistry. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 35 publications
(38 reference statements)
4
49
0
Order By: Relevance
“…Lung tissue expresses both 1α-hydroxylase, the enzyme that converts 25(OH)D to the metabolically active 1,25-hydroxyvitamin D (1,25(OH) 2 D) (31), and the vitamin D receptor (VDR) which mediates the anti-proliferative and other effects of 1,25(OH) 2 D (32). Furthermore, experimental studies have observed that higher VDR expression in lung tumors is associated with improved survival (33) and that vitamin D inhibits metastasis and angiogenesis in lung cancer cells (4, 5). Select characteristics of the ATBC cohort may have contributed to the weak findings observed in the current study as well as a previous analysis in ATBC of serum 25(OH)D concentration and risk of lung cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Lung tissue expresses both 1α-hydroxylase, the enzyme that converts 25(OH)D to the metabolically active 1,25-hydroxyvitamin D (1,25(OH) 2 D) (31), and the vitamin D receptor (VDR) which mediates the anti-proliferative and other effects of 1,25(OH) 2 D (32). Furthermore, experimental studies have observed that higher VDR expression in lung tumors is associated with improved survival (33) and that vitamin D inhibits metastasis and angiogenesis in lung cancer cells (4, 5). Select characteristics of the ATBC cohort may have contributed to the weak findings observed in the current study as well as a previous analysis in ATBC of serum 25(OH)D concentration and risk of lung cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…For this study we measured the nuclear VDR expression level in colorectal cancer tissue because VDR modulates genomic transcription in cell nuclei (1, 7) and the nuclear VDR level—not the cytoplasmic VDR level—has been a prognostic marker of improved survival (20, 21). We retrieved formalin-fixed paraffin-embedded colorectal cancer tissue blocks from hospitals throughout the United States where colorectal cancer patients had undergone surgical resection.…”
Section: Methodsmentioning
confidence: 99%
“…While PEA3 plays a key role in metastasis of lung cancer cells, an increase in VDR expression in lung cancer has been associated with improved survival in patients with AC (58, 59). Moreover, associations between VDR and surfactant physiology have been previously described.…”
Section: Discussionmentioning
confidence: 99%